Integration Mechanisms and Performance in Port–Hinterland Supply Chains: A Systematic Review - Hao Zhang; Mark Ching-Pong Poo; Yui-yip Lau; Shiqi Fan (Journal of Marine Science and Engineering, 2026)
Port–hinterland links are a major driver of performance in maritime supply chains, affecting landed cost, service reliability and environmental outcomes. Yet research on ports and inland freight remains fragmented across transport geography, logistics, operations research and governance studies. This review consolidates evidence on how physical, operational, governance and digital integration levers shape supply chain outcomes at the port–hinterland interface. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-informed protocol was applied to Web of Science Core Collection records retrieved with a title-level port–hinterland query, last updated on 23 November 2025. The qualitative synthesis covers 90 peer-reviewed studies published from 2008 to 2026. Four eligible records (IN22, IN30, IN54 and IN83) could not be retrieved as full texts and are excluded from the qualitative synthesis; their metadata are retained only in the 94-record bibliometric keyword layer. The review traces the evolution from spatial and administrative views of hinterlands toward functional, network-based and actor-centred perspectives, and synthesises seven streams: delimitation and port choice, corridor competition, dry ports and extended gates, coordination and governance, multimodal operations, digitalisation, and sustainability and resilience. It proposes a four-layer conceptual framework linking infrastructure, services, governance and information integration to cost, reliability, capacity, emissions and resilience. The evidence base remains dominated by model-based studies that offer limited causal identification, supporting a focused agenda for more empirically grounded port–hinterland supply chain research.

Population dynamics and cell size structure of Karenia mikimotoi during an algal bloom event in Hakodate Bay, Japan - Hoi Ching Lau; Akihide Kasai; Shoko Tatamisashi; Masahide Wakita; Kwee Siong Tew; Kohei Matsuno (Regional Studies in Marine Science, 2026)

Resilience and Adaptability Analysis of Port-Centric Transport Networks for Meteorological Disasters: A Case of Shanghai Port - Tianni Wang; Tina Ziting Xu; Zongjie Ding; Mei Sha; Lingzhi Ye; Junqing Tang; Mark Ching-Pong Poo; Yui-yip Lau; Chengpeng Wan (Journal of Marine Science and Engineering, 2026)
Climate change has intensified the frequency and severity of meteorological disasters, posing significant challenges to the resilience and adaptability of port-centric transport networks (PCTNs) and global trade stability. Unlike previous studies that adopt generalised resilience frameworks or treat disaster types uniformly, this study develops a disaster-specific, integrated assessment framework whose novelty lies in coupling three complementary methods, each playing a distinct role: (i) integer programming optimises post-disaster recovery decisions under budgetary constraints by selecting cost-effective measures that maximise re-stored container-handling capacity; (ii) Monte Carlo simulation (10,000 iterations) captures the stochastic nature of meteorological disruptions and quantifies probabilistic resilience under typhoons, storm surges, and heavy fog; and (iii) an Analytic Hierarchy Process–Evidence Reasoning (AHP–ER) hybrid integrates subjective expert judgement with objective field data to evaluate adaptability across a four-level indicator system, thereby reducing the subjectivity of conventional multi-criteria approaches. Applied to Shanghai Port, the framework yields normalised resilience scores on a [0, 1] scale, where 1.0 denotes full operational continuity (network throughput equals demand) and values below 0.80 indicate substantial disruption requiring urgent intervention. Heavy fog produces the lowest score (0.73, ‘moderate-to-severe disruption’), followed by typhoons (0.81, ‘mild disruption’) and storm surges (0.89, ‘near-normal operation’), revealing that low-visibility events—not high-energy storms—pose the dominant operational threat at Shanghai Port. Translating these findings into practice, the study recommends the following: (1) deploying real-time visibility-monitoring (LiDAR) and AI-driven traffic-scheduling systems to mitigate fog-related disruptions; (2) reinforcing gantry-crane anchoring and prepositioning emergency power supplies in typhoon-prone berths; (3) prioritising hinterland-port handling redundancy in Jiangsu and Anhui sub-networks (adaptability scores 0.639 and 0.642); and (4) piloting an integrated Shanghai–Zhejiang cross-regional emergency-response corridor with shared berthing rights and standardised joint drills. These targeted, quantitatively grounded recommendations offer port authorities and policymakers an evidence base for prioritising infrastructure investment and organisational reform to safeguard global supply chains against escalating climatic threats.

What matters for renewable energy adoption? A review from consumers’ perspective - Kwang-Jing Yii; Lin-Sea Lau; Cheong-Fatt Ng; Suet-Ling Ching (Environment, Development and Sustainability, 2026)
There has been a recent shift from the usage of fossil fuels to renewable energy due to increased awareness of environmental quality. Although governments have taken various actions to promote the usage of renewable energy, consumer behaviour is also important. This study reviews the literature on the factors that influence renewable energy adoption among consumers. We use the PRISMA protocol for systematic reviews to select the relevant articles about consumers’ renewable energy consumption over the period from 2000 to 2020. The findings and discussion consist of (1) the profile of the studies, such as publication outlets, authorship, and publication trends; (2) theories on renewable energy adoption; and (3) factors influencing consumer adoption of renewable energy. Most importantly, based on our findings, we propose a framework of very important factors (willingness to pay, price or cost, knowledge, and government policies), moderately important factors (public awareness), and less important factors (perceived benefits and social influence). This study also provides key implications for researchers, suppliers, and policymakers. We also synthesize the findings with an analysis of different dimensions, identifying future research directions on renewable energy adoption, which include suggestions for examining political and regulatory factors, comparative studies between countries, and considering the suppliers’ perspective.

Emergence of Next-Generation Sequencing for Laboratory Diagnosis of Talaromyces marneffei - Fanfan Xing; Chaowen Deng; Zhendong Luo; Chi-Ching Tsang; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2026)
The first case of Talaromyces marneffei infection diagnosed by next-generation sequencing (NGS) was reported in 2018. By 31st December 2024, the number of T. marneffei infections picked up by NGS has increased to a total of at least 241. Most cases were reported from China, reflecting both the regional importance of this infection and its widespread use of NGS for laboratory diagnosis of infectious diseases. Among the cases with clinical details reported, 136 were HIV-negative, which was probably the main reason why T. marneffei was not suspected and the diagnosis was subsequently made with the use of NGS. For these 136 HIV-negative patients, 62 were confirmed to have other forms of immunodeficiencies, such as anti-interferon gamma autoantibodies and post-renal/liver transplantation. The clinical presentations were usually non-specific. At least 18 patients were clinically diagnosed as tuberculosis, and empirical anti-tuberculosis therapy was prescribed to 13 patients and NGS was performed because they did not respond to or deteriorated while on anti-tuberculosis treatment. Apart from infectious diseases, at least another 11 patients were initially misdiagnosed to have benign or malignant tumours, the most common being carcinoma of the lung. The median time for detection of T. marneffei by NGS was 2 (range 1–6) days, which is significantly shorter than the median time for detection by fungal culture [7 (range 5–17) days] ( P < 0.0001 by Mann–Whitney U test). NGS has emerged as a promising diagnostic tool for T. marneffei infections, especially for picking up cases in HIV-negative patients and rapid diagnosis.

Development of a colorimetric loop-mediated isothermal amplification (cLAMP) assay for the rapid and visual detection of Aeromonas dhakensis infection in aquaculture - Suat Moi Puah; Wei Ching Khor; Yen Ching Lim; Kyaw Thu Aung; Tien-Tien Vicky Lau; Chen Chen Yong; Po Teen Lim; Chui Pin Leaw; Kek Heng Chua (Aquaculture, 2025)

Port resilience to climate change in the Greater Bay Area - Zhisen Yang; Yui-yip Lau; Mark Ching-Pong Poo; Jingbo Yin; Zaili Yang (Transportation Research Part D: Transport and Environment, 2025)

Repeated Mitochondrial Capture With Limited Genomic Introgression in a Lizard Group - Wesley J. Read; Rebecca J. Laver; Ching Ching Lau; Craig Moritz; Stephen M. Zozaya (Molecular Ecology, 2025)
Mitochondrial introgression is common among animals and is often first identified through mitonuclear discordance—discrepancies between evolutionary relationships inferred from mitochondrial DNA (mtDNA) and nuclear DNA (nuDNA). Over recent decades, genomic data have also revealed extensive nuclear introgression in many animal groups, with implications for genetic and phenotypic diversity. However, the extent to which mtDNA introgression corresponds to nuDNA introgression varies. Here, we investigated historical and recent introgression in the Gehyra nana ‐occidentalis clade, a complex group of Australian geckos with documented cases of mitonuclear discordance suggestive of repeated mtDNA introgression. We hypothesised that mitonuclear discordance in this clade reflects mtDNA introgression with substantial nuclear introgression. Despite evidence of repeated mtDNA introgression, however, we found little to no evidence of historical nuDNA introgression using exon capture and genome‐wide single nucleotide polymorphism (SNP) data. We also found no evidence of gene flow at modern contact zones and detected only a single early generation hybrid. Unsurprisingly, given these results, we found no evidence of transgressive, intermediate, or more variable morphological phenotypes in taxa with introgressed mtDNA. These findings suggest that hybridisation in this system has, at least in some cases, resulted in repeated mitochondrial introgression with little or no nuclear introgression. This pattern aligns with other studies showing limited nuDNA introgression in taxa with mitonuclear discordance, highlighting a potentially broader trend in animal radiations.

Assessing vessel pollution risk in Asian areas: A comparative analysis based on data-driven Bayesian Network approach - Yui-yip Lau; Zhisen Yang; Jingbo Yin; Zhimei Lei; Mark Ching-Pong Poo (Ocean & Coastal Management, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Emergence and Rapid Diagnosis of Talaromyces marneffei Infections in Renal Transplant Recipients by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Shan Zou; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
In the last few years, next-generation sequencing (NGS) has emerged as a technology for laboratory diagnosis of many culture-negative infections and slow-growing microorganisms. In this study, we describe the use of metagenomic NGS (mNGS) for rapid diagnosis of T. marneffei infection in a 37-year-old renal transplant recipient who presented with chronic pneumonia syndrome. Bronchoalveolar lavage for mNGS was positive for T. marneffei sequence reads. Prolonged incubation of the bronchoalveolar lavage revealed T. marneffei colonies after 6 days of incubation. Analysis of 23 cases of T. marneffei infections in renal transplant recipients from the literature revealed that the number of cases ranged from 1 to 4 cases per five years from 1990 to 2020; but increased rapidly to 9 cases from 2021 to 2023, with 7 of them diagnosed by NGS. Twenty of the 23 cases were from T. marneffei -endemic areas [southern part of mainland China ( n = 9); Hong Kong ( n = 4); northeastern India ( n = 2); Indonesia ( n = 1) and Taiwan ( n = 4)]. For the 3 patients from non- T. marneffei -endemic areas [United Kingdom ( n = 2) and Australia ( n = 1)], they had travel histories to China and Vietnam respectively. The time taken for diagnosis by mNGS [median 1 (range 1 to 2) day] was significantly shorter than that for fungal culture [median 6 (range 3 to 15) days] ( P = 0.002). mNGS is useful for picking up more cases of T. marneffei infections in renal transplant recipients as well as providing a rapid diagnosis. Talaromycosis is an emerging fungal infection in renal transplant recipients.

Model validation and applications of wave and current forecasts from the Hong Kong Observatory's Operational Marine Forecasting System - Wai Kong; Ching-chi Lam; Dick-shum Lau; Chi-kin Chow; Sze-ning Chong; Pak-wai Chan; Ngo-ching Leung (Ocean Modelling, 2024)

Risk Analysis of Pirate Attacks on Southeast Asian Ships Based on Bayesian Networks - Qiong Chen; Jinsheng Zhang; Jiaqi Gao; Yui-Yip Lau; Jieming Liu; Mark Ching-Pong Poo; Pengfei Zhang (Journal of Marine Science and Engineering, 2024)
As a bridge for international trade, maritime transportation security is crucial to the global economy. Southeast Asian waters have become a high-incidence area of global piracy attacks due to geographic location and complex security situations, posing a great threat to the development of the Maritime Silk Road. In this study, the factors affecting the risk of pirate attacks are analyzed in depth by using the Global Ship Piracy Attacks Report from the IMO Global Integrated Shipping Information System (GISIS) database (i.e., 2013–2022) in conjunction with a Bayesian Network (BN) model, and the Expectation Maximization algorithm is used to train the model parameters. The results show that piracy behaviors and the ship’s risk are the key factors affecting the risk of pirate attacks, and suggestions are made to reduce the risk of pirate attacks. This study develops a theoretical basis for preventing and controlling the risk of pirate attacks on ships, which helps maintain the safety of ship operations.

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

Maritime transport resilience: A systematic literature review on the current state of the art, research agenda and future research directions - Yui-yip Lau; Qiong Chen; Mark Ching-Pong Poo; Adolf K.Y. Ng; Chung Chui Ying (Ocean & Coastal Management, 2024)

Emerging patterns of genetic diversity in the critically endangered Malayan tiger (Panthera tigris jacksoni) - Kate Allberry; Jeffrine Japning Rovie-Ryan; Nur Alizati Nabila Giarat Ali; Nurul-Ain Elias; Mark Rayan Darmaraj; Christopher Chai Thiam Wong; Lau Ching Fong; Olutolani Smith; Khairul Amirin Bin Mohamed; Mohamad Izereen Bin Amat Mukri; Muhammad Hafiz Bin Mohd Yazid; Matthew J. Struebig; et al. (Biodiversity and Conservation, 2024)
Southeast Asia experiences some of the highest deforestation in the world. Loss of tropical forest typically leads to widespread habitat fragmentation, with detrimental effects on dispersal ability and gene flow—particularly for large carnivores. We conducted mtDNA and microsatellite analysis to assess—for the first time—contemporary patterns of genetic diversity in the Malayan tiger. We collected 295 suspected carnivore samples in Peninsular Malaysia, from which we identified 26 as originating from tiger using 16 polymorphic microsatellite loci, comprising 22 individual tigers. Despite limitations of the study, our findings suggest tiger subpopulations in the north of the peninsula maintain some genetic connectivity and migration between two putative geographic subpopulations in the Main Range and Greater Taman Negara, with negligible population segregation due to dispersal barriers such as road infrastructure. We identified consistently lower levels of genetic diversity in tigers in the Greater Taman Negara region compared to tigers in the Main Range and small but emerging differences in nuclear and mitochondrial genetic diversity. Our mtDNA haplotype and nuclear DNA analyses suggest the levels of genetic diversity in Malayan tigers may be amongst some of the lowest of the surviving tiger subspecies, though the study is limited both in scale and genomic loci. Our findings are consistent with an expected lag between the rapid decline of tigers in Peninsular Malaysia by over 95% in the last 70 years and observed differences in their levels of genetic diversity.

Vulnerability analysis of cruise shipping in ASEAN countries facing COVID-19 pandemic - Mark Ching-Pong Poo; Zaili Yang; Yui-yip Lau (Ocean & Coastal Management, 2024)

Exploring multiplex qPCR as a diagnostic tool for detecting microfilarial DNA in dogs infected with Dirofilaria immitis: A comparative analysis with the modified Knott’s test - Daisy Ching-Wai Lau; Rosemonde Isabella Power; Jan Šlapeta (Veterinary Parasitology, 2024)

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

The use of immobilised bacteria cross-linked within magnetic alginate beads enhances the treatment of benzophenone-type UV filter chemicals by the SBR system - Sai Hung Lau; Ching-Lun Su; Ting-Yu Yu; YuYing Zhong; XinYuan Xu; Wann-Neng Jane; Yi-Tang Chang (Chemosphere, 2023)

The photometric observation of the quasi-simultaneous mutual eclipse and occultation between Europa and Ganymede on 22 August 2021 - Chu Wing So; Godfrey Ho Ching Luk; Giann On Ching Chung; Po Kin Leung; Kenneith Ho Keung Hui; Jack Lap Chung Cheung; Ka Wo Chan; Edwin Lok Hei Yuen; Lawrence Wai Kwan Lee; Patrick Kai Ip Lau; Gloria Wing Shan Cheung; Prince Chun Lam Chan; et al. (Icarus, 2023)

Biological treatment of benzophenone-type UV filter wastewater in a sequencing batch reactor (SBR) - Ching-Lun Su; Sai Hung Lau; Hsiang-Yuan Yeh; Yi-Tang Chang (International Biodeterioration & Biodegradation, 2023)

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Income inequality, educational attainment and environmental degradation: evidence from global panel - Suet-Ling Ching; Lin-Sea Lau; Chee-Keong Choong (Environmental Science and Pollution Research, 2022)

Is food production vulnerable to environmental degradation? A global analysis - Suet-Ling Ching; Kwang-Jing Yii; Cheong-Fatt Ng; Chee-Keong Choong; Lin-Sea Lau (Environmental and Ecological Statistics, 2021)

Utilizing attached hard ticks as pointers to the risk of infection by Babesia and Theileria species in sika deer (Cervus nippon yesoensis), in Japan - Elzahara Elbaz; Mohamed Abdallah Mohamed Moustafa; Kyunglee Lee; Alice Lau Ching Ching; Michito Shimozuru; Mariko Sashika; Ryo Nakao; Sabry Ahmed El-khodery; Toshio Tsubota (Experimental and Applied Acarology, 2020)

Effects of Potential Probiotic Strains on the Fecal Microbiota and Metabolites of d-Galactose-Induced Aging Rats Fed with High-Fat Diet - Lee-Ching Lew; Yan-Yan Hor; Mohamad-Hafis Jaafar; Amy-Sie-Yik Lau; Boon-Yin Khoo; Sreenivasan Sasidharan; Sy-Bing Choi; Kee-Leong Ong; Tamotsu Kato; Yumiko Nakanishi; Hiroshi Ohno; Min-Tze Liong (Probiotics and Antimicrobial Proteins, 2020)

Sixty Years from Segretain’s Description: What Have We Learned and Should Learn About the Basic Mycology of Talaromyces marneffei? - Chi-Ching Tsang; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2019)

Screening for a Potent Antibacterial Peptide to Treat Mupirocin-Resistant MRSA Skin Infections - Siew Mei Samantha Ng; Hui Si Vivian Ching; GuiFang Xu; Fui Mee Ng; Esther H. Q. Ong; Qiu Ying Lau; Roland Jureen; Jeffrey Hill; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2017)

The Narrow-Spectrum HDAC Inhibitor Entinostat Enhances NKG2D Expression Without NK Cell Toxicity, Leading to Enhanced Recognition of Cancer Cells - Shiguo Zhu; Cecele J. Denman; Zehra S. Cobanoglu; Simin Kiany; Ching C. Lau; Stephen M. Gottschalk; Dennis P. M. Hughes; Eugenie S. Kleinerman; Dean A. Lee (Pharmaceutical Research, 2015)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

Development of a simple chromatographic method for distinguishing between two easily confused species, Hedyotis diffusa and Hedyotis corymbosa - Clara B.S. Lau; Ling Cheng; Bobby W.H. Cheng; Grace G.L. Yue; Eric C.W. Wong; Ching-Po Lau; Ping-Chung Leung; Kwok-Pui Fung (Natural Product Research, 2012)

Acoustic Radiation Force Impulse (ARFI) Imaging of Zebrafish Embryo by High-Frequency Coded Excitation Sequence - Jinhyoung Park; Jungwoo Lee; Sien Ting Lau; Changyang Lee; Ying Huang; Ching-Ling Lien; K. Kirk Shung (Annals of Biomedical Engineering, 2012)

Identification of QTL genes for BMD variation using both linkage and gene-based association approaches - Gloria Hoi-Yee Li; Ching-Lung Cheung; Su-Mei Xiao; Kam-Shing Lau; Yi Gao; Cora H. Bow; Qing-Yang Huang; Pak-Chung Sham; Annie Wai-Chee Kung (Human Genetics, 2011)

Erratum to: Survey of familial glioma and role of germline p16 INK4A /p14 ARF and p53 mutation - Lindsay B. Robertson; Georgina N. Armstrong; Bianca D. Olver; Amy L. Lloyd; Sanjay Shete; Ching Lau; Elizabeth B. Claus; Jill Barnholtz-Sloan; Rose Lai; Dora Il’yasova; Joellen Schildkraut; Jonine L. Bernstein; et al. (Familial Cancer, 2010)

Survey of familial glioma and role of germline p16 INK4A /p14 ARF and p53 mutation - Lindsay B. Robertson; Georgina N. Armstrong; Bianca D. Olver; Amy L. Lloyd; Sanjay Shete; Ching Lau; Elizabeth B. Claus; Jill Barnholtz-Sloan; Rose Lai; Dora Il’yasova; Joellen Schildkraut; Jonine L. Bernstein; et al. (Familial Cancer, 2010)